Out of Pocket Spending for Febrile Illnesses among Children Admitted to Two Teaching Hospitals in Sri Lanka (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: out of focket spending; doctor patient communication; target population; acute febrile illness